ANALISIS PEMOTONGAN, PENYETORAN DAN PELAPORAN PPh FINAL ATAS LELANG TANAH DAN/ ATAU BANGUNAN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SURABAYA - Rini Kartikasari; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2021)
The objectives of this research are 1) To analyze the final PPh deduction for land and / or building auction 2) To analyze final PPh payment for land and / or building auction and 3) To analyze the final PPh report on land and / or building auction at the Service Office State Assets and Surabaya Auctions. This type of research uses descriptive qualitative analytical methods. In this study, data analysis was carried out using qualitative data analysis techniques, because the data obtained were descriptions. Data analysis in qualitative research was carried out at the time of data collection. The final PPh deduction for land and / or building auction at the Surabaya State Wealth and Auction Service Office shows a decrease in the achievement of the auction principal realization with the lowest achievement, namely in 2020, reaching 76.74%. The auction principal is obtained from the price agreement between the buyer and the auction official. After the auction principal price is established, the buyer is required to make full payment before the deadline set by the auction official, the deadline for redemption is usually 5 (five) working days after the date of the minutes of auction. The buyer makes full payment of the auction principal price through the treasury's account of receipt. Furthermore, the revenue treasurer will deduct Final Income Tax through a detailed calculation made by the auction official with a tax rate of 2.5%. Final PPh reporting on land and / or building auction at the Surabaya State Wealth and Auction Service Office, it can be seen that after the deposit process has been completed, reporting will be carried out by the auction department.Keywords: Cutting, Deposit and Final Pph Final Reporting on Land and / or Building Auction